Development of Medicines for Rare Pediatric Diseases - Danilo Marimpietri; Guendalina Zuccari (MDPI AG, 2023)
To date, approximately 7000 rare diseases exist, affecting between 6% and 8% of the global population and >30 million people in the European Union [...]